Search for high-mass states with one lepton plus missing transverse momentum in proton–proton collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
The ATLAS detector is used to search for high-mass states, such as heavy charged gauge bosons (W', W∗), decaying to a charged lepton (electron or muon) and a neutrino. Results are presented based on the analysis of pp collisions at a center-of-mass energy of 7 TeV corresponding to an integrated luminosity of 36 pb-1. No excess beyond standard model expectations is observed. A W' with sequential standard model couplings is excluded at 95% confidence level for masses below 1.49 TeV, and a W∗ (charged chiral boson) for masses below 1.35 TeV.